Personal data protection of a «digital» citizen in a library - Z. V. Rodionova; L. K. Bobrov; I. P. Medyankina (Библиосфера, 2018)
The article analyzes main aspects of personal data protection in the context of modern library transition to the digitized environment. It represents the algorithm of classifying personal data information system in the library sphere. Authors review the most frequent law violation in the field of personal data protection by the library staff.